Time-resolved 3D imaging of ultrafast spin–orbit wave packet dynamics. (13th March 2019) - Bayer, Tim; Gräfing, Daniela; Kerbstadt, Stefanie; Pengel, Dominik; Eickhoff, Kevin; Englert, Lars; Wollenhaupt, Matthias
Abstract: We combine bichromatic polarization pulse shaping with photoelectron imaging tomography for time-resolved spatial imaging of ultrafast spin–orbit wave packet (SOWP) dynamics in atoms. Polarization-shaped two-color pump-probe sequences are generated by spectral amplitude and phase modulation of a femtosecond input pulse and used to excite SOWPs in the potassium 4 p fine-structure doublet. By selecting different spectral bands for pump and probe pulse, we achieve interference-free detection of the spatiotemporal SOWP dynamics. Using tomographic techniques, we reconstruct the three-dimensional photoelectron momentum distribution (3D-ED) created by the probe pulse. Time-resolved measurement of the 3D-ED reveals the orbital realignment dynamics induced by spin–orbit interaction in the neutral atom.